PENGARUH KOMPOSISI BIOAKTIVATOR KOTORAN SAPI DAN DAUN GAMAL (GLIRICIDIA SEPIUM) DENGAN NUTRISI UBI JALAR TERHADAP KUALITAS KOMPOS - Tawa, Bibiana D.; Tnunay, Yarni R.; Suwari, Suwari; Nitbani, Febri O. (Chemistry Notes, 2020)
A research conducted about effect of bioaktivator of cow feces and gamal (gliricidiasepium) leaves with sweet potato nutrition toward the compost quality. This research hadpurpose to know the compost characteristics of cow`s dung composition and gamal. Thecharacteristic determined to 60% of cow`s dung and 40% gamal leaves used purple sweetpotatoes nutrition and water that made constant. The variation of cow`s dung and gamal leaveswas 90%: 10%, 50%: 50%, 30%: 70%. The research result show that in the 14th days therewere compost characteristics to produce compost based on SNI 19-7030-2004 andrequirements of the minister of agriculture number 70/Permentan/SR.140/10/2011. Thevariations of cow`s dung and gamal leaves did not effect towards C/N ratio compost.